2022
DOI: 10.15557/jou.2022.0020
|View full text |Cite
|
Sign up to set email alerts
|

Summary of meta-analyses of studies involving TIRADS classifications (EU-TIRADS, ACR-TIRADS, and K-TIRADS) in evaluating the malignant potential of focal lesions of the thyroid gland

Abstract: Numerous scientific societies around the world have published their TIRADS (Thyroid Imaging Reporting and Data System) classifications that evaluate the risk of malignancy of focal thyroid lesions, presenting different ultrasound features for each category and lesion size thresholds to determine eligibility for biopsy. The use of such risk estimation systems in focal thyroid lesions facilitates the reporting of thyroid ultrasound findings and improves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…EU-TIRADS categories have been observed to be related to thyroid nodules malignancy, although the performance of such system should be improved and therefore a FNAB is currently recommended in all EU-TIRADS ≥4 nodules ( 50 , 72 75 ), as cancer underdiagnosis rate rises to 37.7% ( 55 , 72 80 ). The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of EU-TIRADS in adulthood are between 70.6-83.5%, 51.2-94.1%, 11.8-76.1% and 85.4-94.9%, respectively ( 62 , 73 75 , 77 , 78 ). The performance of EU-TIRADS in paediatric age has been evaluated in a few studies that showed lower efficacy than in adults, with sensitivity, specificity, PPV and NPV ranging between 41.7-100%, 25-75.9%, 41.7-44%, 75.9-100% respectively ( 63 , 78 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EU-TIRADS categories have been observed to be related to thyroid nodules malignancy, although the performance of such system should be improved and therefore a FNAB is currently recommended in all EU-TIRADS ≥4 nodules ( 50 , 72 75 ), as cancer underdiagnosis rate rises to 37.7% ( 55 , 72 80 ). The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of EU-TIRADS in adulthood are between 70.6-83.5%, 51.2-94.1%, 11.8-76.1% and 85.4-94.9%, respectively ( 62 , 73 75 , 77 , 78 ). The performance of EU-TIRADS in paediatric age has been evaluated in a few studies that showed lower efficacy than in adults, with sensitivity, specificity, PPV and NPV ranging between 41.7-100%, 25-75.9%, 41.7-44%, 75.9-100% respectively ( 63 , 78 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of EU-TIRADS in adulthood are between 70.6-83.5%, 51.2-94.1%, 11.8-76.1% and 85.4-94.9%, respectively ( 62 , 73 75 , 77 , 78 ). The performance of EU-TIRADS in paediatric age has been evaluated in a few studies that showed lower efficacy than in adults, with sensitivity, specificity, PPV and NPV ranging between 41.7-100%, 25-75.9%, 41.7-44%, 75.9-100% respectively ( 63 , 78 , 79 ). The data from our study confirm the significant correlation of the EU-TIRADS category with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The exploration of the nodules involves a clinical examination, completed by an ultrasound using the EU-TIRADS score, the hormonal dosage, the cytopuncture, using the Bethesda score and, of course, the biopsy after the surgery [ 5 , 6 , 7 , 8 , 9 , 10 ]. Thyroid ultrasound has become a key examination in the management of thyroid nodules [ 2 , 10 , 11 , 12 , 13 ]. In countries with sufficient iodine intake, clinical-based prevalence of thyroid nodules amounts to 5.3–6.4% in women and 0.8–1.6% in men.…”
Section: Introductionmentioning
confidence: 99%
“…den nationalen und internationalen Leitlinien als Basisdiagnostik für die Beurteilung von Schilddrüsenknoten benannt [3,4]. Die Einführung sonografischer Risikostratifizierungssysteme (TIRADS) spielt dabei eine zentrale Rolle [5]. Zudem besitzt die Methode einen hohen Stellenwert bei der Behandlung von Autoimmunerkrankungen und Thyreoiditiden, in der Verlaufskontrolle nach Schilddrüsentherapien und in der Nachsorge von Schilddrüsenkarzinomen [2,6,7].…”
unclassified